Drug use patterns and related factors among female sex workers in Iran in 2019-2020: results from Integrated Bio-Behavioral Surveillance-III (IBBS-III) - Bushra Zareie; Mohammad Aziz Rasouli; Mohammad Mehdi Gouya; Samaneh Akbarpour; Fatemeh Hadavandsiri; Elham Rezaei; Yousef Moradi; Ali Soltani; Ghobad Moradi (BMC, 2023)
Abstract Introduction Drug use is highly prevalent among female sex workers (FSWs). Some forms of drug use, such as injecting drug users (IDU), put them at greater risks for HIV and blood born disease (BBD). In this study, the pattern of drug use and its related factors among Iranian FSWs were investigated. Materials and methods This cross-sectional study was performed based on the data of the integrated bio-behavioral surveillance-III (IBBS-III) on FSWs in 8 cities of Iran using the respondent-driven sampling (RDS) method conducting in 2019-2020. Of the 1515 FSWs participating in the IBBS-III study, 1,480 answered questions about drug use. To calculate the prevalence of drug use lifetime and in the past month, weighted analysis was used. Univariate and multivariate logistic regression was used to investigate the factors related to drug use. Results The prevalence of lifetime drug use and the prevalence of current drug use (single and poly drug use) among FSWs were estimated to be 29.3% and 18.86%, respectively. According to multivariate regression analysis, the odds ratio (odds) of lifetime drug use showed a statistically significant association with lower education (AOR = 1.18; 95% CI: 1.07-1.3), being a direct sex worker (AOR = 1.77; 95% CI: 1.21-2.61), working in team houses or hangouts (AOR = 1.51; 95% CI: 1.10-2.06), a history of intentional abortion (AOR = 1.41; 95% CI: 1.07-1.87), condom use in the last sex (AOR = 1.61; 95% CI: 1.19-2.17), a history of imprisonment (AOR = 3.05; 95% CI: 2.25-4.14), HIV positive tests (AOR = 8.24; 95% CI: 1.66-40.9), alcohol use (AOR = 1.69; 95% CI: 1.29-2.29), and finding sexual clients in places such as parties, shopping malls, streets, and hotels, or by friends (AOR = 1.46; 95% CI: 1.01-2.12). Conclusion Given that drug use among FSWs is about 14 times higher than that of the Iranian general population, it is imperative that drug reduction programs be integrated into service packages. Specifically, prevention programs should be prioritized for occasional drug users within this population as they are at a greater risk of developing drug use issues compared to the general population.